2013
DOI: 10.1146/annurev-soc-071312-145650
|View full text |Cite
|
Sign up to set email alerts
|

Social Scientific Inquiry Into Genocide and Mass Killing: From Unitary Outcome to Complex Processes

Abstract: This article reviews social scientific research on the occurrence of genocide and mass killing, focusing on the underlying, contributing processes. Relevant studies are grouped by their primary analytic focus: (a) macro-level state and institutional processes, (b) political elites and policy decisions, (c) nonelite perpetrator motivation and participation, (d) social construction of victim group identity, and (e) local and regional variation within larger episodes. We also discuss issues relating to the concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…It may be more accurate to understand this state, and likely any geographic area, in terms of its diverse "microclimates" of ethnic contention (Ward 2014), where mobilization is ultimately contingent on a range of contextual factors. Similar insights have informed studies of mass collective violence, which seek to identify meso-and microlevel mechanisms that variously mobilize or demobilize adherents across divergent social environments (Karstedt 2013;Owens, Su, and Snow 2013). Interestingly, as our legacies of racial violence and propinquity findings indicate, and the distinct local history and statewide role of Rowan County best illustrates, these microclimates are not confined spatially or temporally, but rather have radiating influences.…”
Section: Comparative Case Analysis: Rowan Countymentioning
confidence: 73%
“…It may be more accurate to understand this state, and likely any geographic area, in terms of its diverse "microclimates" of ethnic contention (Ward 2014), where mobilization is ultimately contingent on a range of contextual factors. Similar insights have informed studies of mass collective violence, which seek to identify meso-and microlevel mechanisms that variously mobilize or demobilize adherents across divergent social environments (Karstedt 2013;Owens, Su, and Snow 2013). Interestingly, as our legacies of racial violence and propinquity findings indicate, and the distinct local history and statewide role of Rowan County best illustrates, these microclimates are not confined spatially or temporally, but rather have radiating influences.…”
Section: Comparative Case Analysis: Rowan Countymentioning
confidence: 73%
“…Although criminologists have devoted little attention to the perpetrators of genocide, other scholars have studied perpetrators across several episodes of genocide, largely focusing on the Holocaust and Rwanda (see Loyle, ; Owens, Su, and Snow, ; Verdeja, ). To date, these studies have reached one enduring conclusion—perpetrators of genocide are “normal.” For example, Browning's Ordinary Men (1998) argued that members of German Police Battalion 101, who committed many murders during the Holocaust, were family men of working‐class backgrounds.…”
Section: Genocide Crime and The Gendered Life Coursementioning
confidence: 99%
“…Meanwhile, scholars have called for greater methodological plurality in social inquiry on atrocities. Writing in the Annual Review of Sociology , Owens, Peter & Su () showed surprise that researchers have yet to utilize “recent advances in comparative configurational methods” to parse out the causal complexity that is commonly assumed to be inherent to genocide and mass killing.…”
Section: Introductionmentioning
confidence: 99%